Pembuatan Pembuatan Video Dokumenter Kesejahteraan Kelompok Rentan Lanjut Usia pada DPRD Kota Bogor (Teknik Editing): - - Zahra, Alya Nur; Hadiyanto, Hadiyanto (Program Study of Islamic Communication and Broadcasting, Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
Editing techniques are one of the most important aspects in making documentary videos. Good editing techniques can help tell interesting stories and improve the visual and audio quality of documentary videos. Editing techniques are carried out by assembling videos, adding visual effects and transitions. Editing techniques are used to increase the need for detailed information that will be presented to the audience. The preparation of stories can be conveyed through narration by emphasizing important points and conveying the message you want to convey and inserting images that are appropriate to the narrative. Displaying images that can increase the detail of information is also important for conveying messages to the audience. This editing process aims to create a coherent video work. So that the documentary video can be well received so that it can increase public awareness about the welfare of vulnerable elderly groups and is suitable for publication through social media owned by the Bogor City DPRD.